Characterisation and cytotoxic screening of metal oxide nanoparticles putative of interest to oral healthcare formulations in non-keratinised human oral mucosa cells in vitro. Issue 1 (25th December 2015) - Best, M.; Phillips, G.; Fowler, C.; Rowland, J.; Elsom, J.
Abstract: Nanoparticles are increasingly being utilised in the innovation of consumer product formulations to improve their characteristics; however, established links between their properties, dose and cytotoxicity are not well defined. The purpose of this study was to screen four different nanomaterials of interest to oral care product development in the absence of stabilisers, alongside their respective bulk equivalents, within a non-keratinised oral epithelial cell model (H376). Particle morphology and size were characterised using scanning electron microscopy (SEM) and dynamic light scattering (DLS). The H376 model showed that zinc oxide (ZnO) was the most cytotoxic material at concentrations exceeding 0.031% w/v, as assessed using the lactate dehydrogenase (LDH) and dimethylthiazolyl-diphenyl-tetrazolium-bromide (MTT) assays. ZnO cytotoxicity does not appear to be dependent upon size of the particle; a result supported by SEM of cell–particle interactions. Differences in cytotoxicity were observed between the bulk and nanomaterial forms of hydroxyapatite and silica (SiO2 ); titanium dioxide (TiO2 ) was well tolerated in both forms at the doses tested. Overall, nano-size effects have some impact on the cytotoxicity of a material; however, these may not be as significant as chemical composition or surface properties. Our data highlights the complexities involved at the nano-scale, in both the characterisation of materials and in relation to cytotoxic properties exerted on oral epithelial cells. Highlights: Nanoparticle cytotoxicity of interest for future oral healthcare formulations. Nanoparticles characterised using SEM and DLS, in the absence of stabilisers. H376 oral epithelial cell model was used for the first time in preliminary screening. Hydroxyapatite, SiO2 and TiO2 nanoparticles were well tolerated in the model. ZnO significantly more cytotoxic than other materials, but were not nano-dependent.